In vitro and in vivo toxicity of 5-FdU-alendronate: a novel cytotoxic bone-seeking duplex drug against bone metastasis - Schott, Sarah; Vallet, Sonia (Investigational new drugs, 2015)
SummaryBackground Bone remains one of the most common anatomic sites for cancer metastases, and the limited therapeutic options aggravate cancer-related morbidity and mortality in multiple malignancies. The covalent conjugation of the amino-bisphosphonate alendronate (ale) with the antimetabolite 5-fluoro-2′-desoxyuridine (5-FdU) results in N4-(butyl-(4-hydroxy-4-phosphono)phosphate)-5-fluoro-2′-desoxyuridine (5-FdU-alendronat, 5-FdU-ale), an effective, novel bone-targeting duplex drug directed against skeletal cancer manifestations. Methods In vitro cytotoxicity of ale, 5-FdU or 5-FdU-ale was measured with Alamar Blue and MUH cell viability assays in 14 malignant melanoma, multiple myeloma, bone marrow-derived stromal cell and osteoblast-like cell lines. In vivo toxicity was evaluated using the chicken embryo assay and evaluation of nephrotoxicity and the systemic toxicity in Balb/c nude mice. The effect of 5-FdU-ale on osteoclast was evaluated with Balb/c nude mice in a metastatic breast cancer mouse model. Results A cell line-specific, dose-related cytotoxicity was observed for 5-FdU-ale in all cancer cell lines tested, which was significantly less toxic than 5-FdU alone when compared to the benign osteoblasts or stromal cells. The embryotoxicity of 5-FdU-ale was significantly less than that of the parental drugs alendronate or 5-FdU. 5-FdU-ale showed no signs of unwanted side effects, weight loss or nephrotoxicity in mice. In a bone metastasis mouse model, 5-FdU-ale reduced the number of tumor-associated osteoclasts. Conclusion The coupling of an amino-bisphosphonate with an antimetabolite via an N-alkyl-bonding offers a new strategy for the preparation of amino-bisphosphonates conjugates with a cancer cell-specific, efficacious cytotoxic bone-targeting potential along with a reduced systemic toxicity. The innovative duplex drug 5-FdU-ale therefore warrants further clinical investigation.